C INVESTIGATION OF HEAT TRANSFER COEFFICIENT AUGMENTATION IN DIVERGENT RECTANGULAR DUCT FOR TWO PHASES FLOW (AIR-WATER) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
In this project, the flow distribution for air and water, and the enhancement of the heattransfer coefficient are experimentally studied. Experimental studies have been performed totest the influence of discharge, pitch, the height of ribs at a constant heat flux on thetemperature and pressure distributions. Along the channel of the test and the heat transfercoefficient, the water volume flow rate was about (5-12 L/min), the air volume flow rate wasabout (5.83-16.66 L/min), and heat were (80, 100,120, watt). An experimental rig wasconstructed within the test whole system. On the other hands, the channel has a divergentsection with an angle =15o with vertical axis. The study included changing in the ribs heightby using three values (12, 15, 18 mm) and changing the ribs pitch into three values (5, 8, 10mm).The results indicated an increasing in the local heat transfer coefficient as a result ofincreasing the discharge. While there was an inverse influence for the temperature distributionalong the test channel which drops when the discharge rise. The results also confirm that theincreasing in the pitch distance leads to reduce the heat transfer coefficient. Increasing theribs height increases the coefficient of heat transfer. However, the experiment heat transfercoefficient improves about (15.6 %) when the water volume flow rate increased from (5 to 12L/min), and about (18.7%) when the air volume flow rate increased from (5.83 to 16.66L/min). The best heat transfer coefficient was about (35.6 %) which can be achieved whenthe pitch decreased from (10 to 5mm). The increasing of the height from (12 to 18) mmimproves the heat transfer coefficient about (11.2 %). The best rib dimension was 18 mmheight, and 5 mm pitch, which give a maximum heat transfer coefficient (1212.02 W/m2. oC).